Adolescents’ Emotional Awareness, Regulation, and Transformation: Emotion-Focused Therapy as Anger Management - Limbadan, Nelly Zosa; Udarbe, Margaret Helen F. (Silliman Journal, 2022)
Aimed at addressing increased violence and aggression in the school setting, this study evaluated the use of Emotion-Focused Therapy (EFT) in managing anger level and intensity of selected adolescents. These adolescents were 16 high school students on Strict Disciplinary Probation status whose level of anger was determined using the Adolescent Anger Rating Scale. The twophase study first consisted of developing a tool to measure the effectiveness of EFT—a tool referred to as the Emotional Awareness, Regulation and Transformation Scale (EARTS). The second phase involved the conduct of the therapy as a psychotherapeutic intervention intended to help selected adolescents deal with anger. A significant improvement was observed from pretest-posttest data on EARTS at the conclusion of the 12-session EFT